2011
DOI: 10.3897/zookeys.154.1963
|View full text |Cite
|
Sign up to set email alerts
|

At the lower size limit for tetrapods, two new species of the miniaturized frog genus Paedophryne (Anura, Microhylidae)

Abstract: I describe two new species in the miniaturized microhylid frog genus Paedophryne from forests in southeastern Papua New Guinea. The first species is described on the basis of two specimens and exhibits female snout-vent length of 8.5–9.0 mm (no males known), whereas that of the second species, described on the basis of 12 specimens, is 8.8–9.3 mm, with males 8.1–8.9 mm. These frogs are smaller than the other two diminutive species described when the genus was recently erected, and they represent what are curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…A number of anuran lineages that approach the minimum size limits for vertebrates have been recently described (Wollenberg et al, 2008; Kraus, 2010a; Rittmeyer et al, 2012; Lehr & Coloma, 2008; Kraus, 2011; Wollenberg et al, 2008; Rittmeyer et al, 2012), and it has been suggested that miniaturised frogs may represent an often overlooked, but important ecological guild in tropical areas (Rittmeyer et al, 2012). Broadly, three patterns are globally apparent in miniaturised frogs: most lack a free-swimming tadpole stage (Estrada & Hedges, 1996); occur in wet tropical and usually insular regions; and are more-or-less terrestrial (Kraus, 2010a; Rittmeyer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A number of anuran lineages that approach the minimum size limits for vertebrates have been recently described (Wollenberg et al, 2008; Kraus, 2010a; Rittmeyer et al, 2012; Lehr & Coloma, 2008; Kraus, 2011; Wollenberg et al, 2008; Rittmeyer et al, 2012), and it has been suggested that miniaturised frogs may represent an often overlooked, but important ecological guild in tropical areas (Rittmeyer et al, 2012). Broadly, three patterns are globally apparent in miniaturised frogs: most lack a free-swimming tadpole stage (Estrada & Hedges, 1996); occur in wet tropical and usually insular regions; and are more-or-less terrestrial (Kraus, 2010a; Rittmeyer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Miniaturization, the evolution of tiny adult body size, is widespread amongst animal taxa and is commonly associated with novel ecological, physiological, and morphological attributes (Hanken & Wake, ). Although perhaps most commonly encountered in groups of marine invertebrates (Hanken & Wake, ; Rundell & Leander, ), species with extremly small adult body size are known from all of the major groups of vertebrates, with many examples from amphibians and fishes (e.g., Britz, Conway, & Rüber, ; Das & Haas, ; Hanken & Wake, ; Kottelat, Britz, Tan, & Witte, ; Kraus, ; Parra‐Olea et al, ; Rittmeyer, Allison, Gründler, Thompson, & Austin, ). The phenotypes of miniaturized taxa are of interest because they represent unique combinations of reductions and structural simplifications often with novel traits that are not developed in their larger relatives (Britz & Conway, ; Hanken & Wake, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the increased risk of desiccation could select for larger body sizes for water conservation (Nevo ; Gouveia and Correia ; Gouveia et al. ) or locomotion and exploitation of leaf‐litter habitats could select for smaller body sizes (Lehr and Coloma ; Lehr and Catenazzi ; Kraus , ). These selective pressures should be similar for males and females, thus we predict that if these mechanisms are at work, size will vary equally in both sexes.…”
mentioning
confidence: 99%
“…We used comparative analyses to test hypotheses about the evolutionary forces behind this reproductive diversification, and explored the potential selective drivers for the evolution of terrestriality. Specifically, we tested three hypotheses: (1) terrestriality evolved only once in this clade, as indicated by an earlier morphological phylogeny (Verdade ); (2) both males and females vary in overall sizes according to reproductive habitats (Nevo ; Lehr and Coloma ; Lehr and Catenazzi ; Kraus ; Kraus ; Gouveia and Correia ; Gouveia et al. ); and (3) males, but not females, decrease in size in terrestrial species because shifts to terrestriality impose lower sexual selection for large body sizes due to lower levels of male‐male competition (Zamudio et al.…”
mentioning
confidence: 99%